Mead’s Theory of The Act. A contribution to the pragmatist turn in cognitive sciences (Nóema, 2019)
The article argues in favour of replacing Dewey’s notion of 'experience' in today's cognitive sciences with Mead’s notion of 'act.' Although Dewey's approach to cognition is an essential contribution to the pragmatist turn of cognitive science and his theory of organic relation is particularly useful for future developments in this field, his notion of 'experience' risks proving to be the weak link in the program of empirical implementation of such a turn. In a perspective that shows a clear empirical intent such as that of the 4E programme, the concept of experience, as intentionally vague and smoky, with its strong metaphysical significance, does not seem to offer a useful operational criterion to exclude from evaluation aspects that should not be considered constitutive of the mental. Moreover, in its openness to the overall determination of the relationship between organism and environment, this notion does not contribute to the definition of the phases that characterize the relational dynamics itself. The essay proposes as a solution to these difficulties to turn the attention to Mead's notion of 'act.' Although Mead's act and Dewey's experience are undoubtedly similar concepts, as the result of elaborations often carried out jointly by the two authors, the act seems more suitable to describe in its different characteristics the ideo-sensori-motor process that characterizes the integrated approach in which perception and action are indissolubly linked. Mead's theory of the act is an epistemological tool particularly useful to the empirical program of the 4E, also offering an interesting contribution to the debate between radical representationalists and enactivists.
Keywords: Act; experience; Mead; Dewey; pragmatism; cognitive science